Hedgehog Signaling in Human Medullary Thyroid Carcinoma: A Novel Signaling Pathway - Bohinc, Brittany (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Locally or widely metastatic medullary thyroid carcinoma (MTC) is difficult to treat, and therapeutic options are limited. Recently, kinase inhibitors have shown partial efficacy in this cancer, but there is a continued need for the development of novel therapeutics. Within this context, the Hedgehog (Hh) pathway has been implicated in several types of human tumors, and early clinical trials with Hh antagonists have validated Hh as a novel therapeutic target. For the first time, we evaluated Hh pathway activity in MTC, and examined the effect of Hh pathway perturbation in highly characterized MTC cell lines. METHODS: We examined immunohistochemical expression of the Hh signaling mediators Sonic Hedgehog (Shh) and Glioblastoma (Gli)2 in paraffin-embedded normal versus histologically characterized human MTC tissue. We examined pharmacologic disruption of Hh signaling in vitro using two established MTC cell lines (TT and MZ-CRC-1). Hh signaling was either pharmacologically activated (SAG) or inhibited (GDC-0449) in MTC cell lines; Hh activity was assessed by quantitative real-time polymerase chain reaction, Western blot analysis, and quantification of cellular growth and apoptotic activity. RESULTS: Our data showed increased expression of Hh signaling factors in human MTC compared to normal tissue. In vitro, activation of the Hh pathway resulted in increased expression of key Hh signaling components Smoothened (Smo) and Gli2. Conversely, inhibition of the Hh pathway decreased expression of these genes, leading to significantly reduced cellular growth and increased apoptosis. CONCLUSIONS: Hedgehog signaling components are markedly upregulated in MTC. Hh pathway inhibitors have potential as novel therapeutic options in patients with metastatic and/or surgically unresectable MTC.